(untitled) (Bioresearch Communications, 2024)
Recipe variation has social, economic, geographical, cultural, and other roots. The Analysis of each recipe’s composition is not plausible from a chemical as well as an economic point of view. Instead, a standardized recipe from a set of similar recipes could be ideal for cooking and chemical analysis of the nutrient composition of cooked recipes. This type of data has been found to be scanty in conventional food composition tables (FCT) across the globe. Recipe calculation from raw ingredients has always been problematic because cooking is regarded as an unpredictable process on every occasion. Therefore, analysis of cooked recipes is preferred for FCTs which are used for more authentic and accurate in menu planning for individual or community health purposes. The present study seeks to partially fill the information gap on compositional data for vegetable and leafy vegetable recipes consumed by the lower to middle-income urban and peri-urban households of Bangladesh because they have been observed to be the main consumer of these recipes. The study was conducted into three phases. In phase I, a recipe survey was conducted among purposely selected housewives (n=100) representing Dhaka (n=33), Rangpur (n=37), Rajshahi (n=18) and Chattogram (n=12) divisions. In phase II, 10 selected homemade vegetable and leafy vegetable recipes were selected and standardized from the most cited recipe list obtained from consecutive recipe surveys. In phase III, chemical analyses for proximate nutrients were carried out followed by compilation of vitamin and mineral values from local and global food composition databases. The result revealed that the Moisture, Ash, Protein, Fat, Total Dietary Fiber and Available Carbohydrate content (g/100 g) and Calorie of the samples ranged from 71.57-83.68%, 1.30-4.94%, 1.17-5.86%, 0.20-9.18%, 2.63-7.28%, 1.43-14.66%, and 64.94 to 126.28 Kcal respectively. Method validation and analytical quality assurance program was carried out along with all standard operating procedure (SOP) to ensure quality data generation. Therefore, the data obtained in this study can be taken as reliable data which will enrich the food composition database of Bangladesh. Bioresearch Commu. 10(2): 1565-1572, 2024 (July)